Phenomenon of Albert Einstein. Centenary reflexions - Maślanka, Krzysztof (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2005)
A sketchy portrait of the genius who has changed physics. What can we learn from his work and life?